Determinants Of Women’s Employment Participation Who Have Toddler In East Java During The Covid-19 Pandemic - Atma Sari; Devanto Shasta Pratomo; Nurul Badriyah (Journal of International Conference Proceedings, 2022)
The current COVID-19 pandemic situation has had an unfavorable impact on Indonesia's employment issues, especially women's employment. Women's work participation is needed to help improve the family's economy during the pandemic. The presence of toddler the household will affect a woman's decision to enter the labor market, because women are faced with a choice between raising children or working. Using Susenas 2021 data, this study aims to exemine the determinants of women's work participation who have toddler in East Java during the Covid 19 pandemic. Based on the results of binary logistic regression, it is known that age, education, area of residence, internet use, household poverty status, husband's employment status in East Java have a significant effect on the participation of women who have toddler in East Java during the Covid 19 pandemic. While the number of members has no significant effect. From this research, it is necessary to implement policies that make it easier for women with toddlers to enter the labor market that favors mothers with working toddlers such as policies on working time, sick leave, maternity leave, and exclusive breastfeeding.